Gut microbiota dynamics in a 1-year follow-up after adult liver transplantation in Northeast China - Zhang, Ruoyan; Qiu, Wei; Sun, Xiaodong; Li, Jing; Geng, Xiaochen; Yu, Shichao; Liu, Ying; Huang, Heyu; Li, Mingyue; Fan, Zhongqi; Li, Mingqian; Lv, Guoyue (Frontiers in Physiology, 2023)
Background: Liver transplantation (LTx) is the most effective treatment for end-stage liver diseases. Gut microorganisms influence the host physiology. We aim to profile the dynamics of gut microbiota in the perioperative period and a 1-year follow-up of LTx recipients in Northeast China. Methods: A total of 257 fecal samples were longitudinally collected from 85 LTx patients using anal swabs from pre-LTx to 1-year post-LTx. A total of 48 fecal samples from end-stage liver disease patients without LTx served as the control. 16S rRNA sequencing was used to analyze gut microbiota diversity, bacterial genera, phenotype classification, and metabolic pathways. Results: The diversity of gut microbiota decreased significantly after transplantation, accompanied by a profound change in the microbial structure, which is characterized by increased abundance of facultative anaerobic bacteria dominated by g_Enterococcus and reduced anaerobic bacteria composition. Predicted functional analysis also revealed disturbances in the metabolic pathway of the gut microbiota. After LTx, the diversity of microbiota gradually recovered but to a less preoperative level after 1 year of recovery. Compared with pre-transplantation, the microbiome structure was characterized by an increase in Acidaminococcus and Acidithiobacillus after 1 year of transplantation. Conclusion: LTx and perioperative treatment triggered gut microbial dysbiosis. The gut microbiota was restructured after LTx to near to but significantly differed from that of pre-LTx.